Four‐Step Domino Reaction Enables Fully Controlled Non‐Statistical Synthesis of Hexaarylbenzene with Six Different Aryl Groups. (16th August 2021) - Grau, Benedikt W.; Dill, Maximilian; Hampel, Frank; Kahnt, Axel; Jux, Norbert; Tsogoeva, Svetlana B.
Abstract: Hexaarylbenzene (HAB) derivatives are versatile aromatic systems playing a significant role as chromophores, liquid crystalline materials, molecular receptors, molecular‐scale devices, organic light‐emitting diodes and candidates for organic electronics. Statistical synthesis of simple symmetrical HABs is known via cyclotrimerization or Diels–Alder reactions. By contrast, the synthesis of more complex, asymmetrical systems, and without involvement of statistical steps, remains an unsolved problem. Here we present a generally applicable synthetic strategy to access asymmetrical HAB via an atom‐economical and high‐yielding metal‐free four‐step domino reaction using nitrostyrenes and α, α‐dicyanoolefins as easily available starting materials. Resulting domino product—functionalized triarylbenzene (TAB)—can be used as a key starting compound to furnish asymmetrically substituted hexaarylbenzenes in high overall yield and without involvement of statistical steps. This straightforward domino process represents a distinct approach to create diverse and still unexplored HAB scaffolds, containing six different aromatic rings around central benzene core. Abstract : A high yielding and scalable metal‐free four‐step linear domino reaction results in functionalized triarylbenzene (TAB) and opens the door for making a broad variety of synthetically challenging hexaarylbenzene (HAB) molecules with six different aryl groups.